lookedup4you: studerende, kunder og online-leksikografi - Geeb, Franziskus (Nordiske Studier i Leksikografi, 2006)
lookedup4you: Students, clients and online lexicography. Seventeen BA students at the University of Applied Sciences, Hamburg, Germany, have developed a lexicographic online reference tool with young users as the target group for a client, Verbraucherzentrale Nordrhein- Westfalen, Germany. The online reference tool is based on a specialist system, an alphabetic approach and search options. For this project, lexicography was defined as an opportunity to structure information and as a tool that would meet the client’s needs. The project included all the processes involved in the production of lexicographic online reference works; the definition of a concept designed to persuade the client; the development of a prototype; testing this prototype in consultation with the future users of the reference work; lemmatisation; writing the articles; the production of images and films; the conceptual design and production of quizzes for the reference work; and all the computer programming and design work necessary for a project of this nature.